A MODEL FOR EVALUATING DRIVERS' MEAN SPEED : USING PSYCHOLOGICAL AND DRIVING SIMULATOR DATA - navid javanbakht; babak mirbaha (Numerical Methods in Civil Engineering)
Driving speed has always played an important role in safety. Many variables influence the driver's behavior to choose the speed, one of which is the individual's psychological variables. In this study, the direct and indirect relationship of a series of psychological variables (latent variables) on the mean speed and the relationship of the latent variables with each other have been investigated. For this purpose, two questionnaires of aggressive drivers and DBQ were used. Also, a driving simulator was used to record the mean speed of the driver . The number of participants is 71 (38% women and 62% men). one proposed model that includes 8 hypotheses was modeled using the structural equation model (partial least square method) that hypotheses were significant at the 99% level. And the results showed that there is a direct relationship between attitude with hostile behavior (H1), hostile behavior with risky violation (H3) , hostile behavior with Self-willed violation (H4), risky violation with Self-willed violation (H5) and Self-willed violation with Inexperience violation/error (H6). subjective norm have inverse relationship with risky violation (H2). Also, people who have a high Self-willed violation usually drive at a high speed (H7).